Peningkatan Pengetahuan dan Ketrampilan Kader Pemantauan Tumbuh Kembang Balita di Posyandu dengan Metode BBM dan Mind Mapping (MM) - Triyanti, Mimin; Widagdo, Laksmono; BM, Syamsulhuda (Jurnal Promosi Kesehatan Indonesia, 2017)
Background: Fostering cadres is an important in improving the knowledge and skills of cadres in Posyandu activities. Skills of cadre will greatly assist in implementation of Posyandu. One of the elements that determine the success of increased knowledge and skills of cadres is the use of learning methods. The aim of the research to determine differences in knowledge and skills of cadres after getting training by learning methods based on problems and methods of learning Mind Mapping.Method: This research use quantitative research with quasi experimental methods, the design of non-randomized control group pre-test and post-test design. Samples are 109 health cadres working at Posyandu Madya which are further divided randomly into two treatment groups and one control group.Results: These results indicate that the cadre training with methods of fuel increased 1.28 more knowledge of the MM group. While the improvement of skill in the fuel group of 1.43 more than the MM group.Keywords:Â  Training of the Cadres, BBM methode, Mind Mapping methodeÂ